Effect of the Fe3+/Cu2+ Ratio on the Removal of the Recalcitrant Oxalic and Oxamic Acids by Electro-Fenton and Solar Photoelectro-Fenton - Salazar-Gonzalez, R (Elsevier Ltd, 2016)
The degradation of 100mL of 2.08mM oxalic acid (OXL) and oxamic acid (OXM) solutions in 0.10M Na2SO4 at pH 3.0 has been studied by solar photolysis (SP), electro-Fenton (EF) and solar photoelectro-Fenton (SPEF). EF and SPEF experiments were performed with a stirred electrochemical cell containing a 3cm2 boron-doped diamond (BDD) anode and a 3cm2 air-diffusion cathode that generates H2O2. Natural sunlight was directly exposed to the solution in SP and SPEF. Catalytic contents of 0.50mM Fe3+, 0.50mM Cu2+ or mixtures up to 0.50mM of both metallic ions were added to the solution and a current density of 33.3mAcm-2 was applied in EF and SPEF. OXM presented a remarkable slower decay than OXL by SP due to the lower photoactivity of metallic-oxamate complexes. OXL concentration decayed 90% in the presence of Fe3+ and Fe3+/Cu2+ mixtures, whereas the OXM drop decreased directly with increasing Cu2+ concentration. In EF, OXL was more slowly removed than OXM due to higher recalcitrant character of the Fe(III)-oxalate complexes which can only be mineralized by OH formed at the anode surface but not by those generated from Fenton s reaction in the bulk. Upon Cu2+ addition, higher removal percentages were found because Cu(II)-carboxylate complexes are attacked by OH, thus accelerating the mineralization. In contrast, OXL destruction was largely enhanced in SPEF using the mixture of catalysts as a result of the photolysis of Fe(III)-oxalate complexes and the parallel mineralization of Cu(II)-carboxylate complexes by the high quantity of oxidant OH induced from photolysis of Fe(III)-aquo species. In all cases, the decay of OXL and OXM concentration obeyed a pseudo-first-order reaction, with an apparent rate constant dependent on the applied current in EF and SPEF. © 2015 Elsevier Ltd.